(untitled) (Research, Society and Development, 2020)
In the current agriculture one of the main limiting factors in soybean yield is the occurrence of dry seasons during the crop cycle. The use of cover crops associated with a no-tillage practice, has been widely used for the improvement of soils and especially in areas of sandy soils, to reduce the effects caused by the low availability of water. Concerning the hypothesis that only the vegetation cover is not enough to solve the effects of water deficit, the objective was to evaluate the combined effect of different irrigation management in a no-tillage system on cultural remains of Brachiaria in different soybean cultivars. The field research was carried out under a center pivot at the Chapadao Foundation, in an area on Braquiaria vegetable residues, where five irrigation depths were implemented and six soybean cultivars in a randomized block design. The following quantitative variables were evaluated: plant height (AP), height of insertion of the first pod (AIV), number of plants (NP), number of pods per plant (NVP), number of grains per pod (NGV), number of grains per plant (NGP), one hundred grain mass (MCG), canopy temperature (DOSSEL) and productivity (PROD), irrigation has an effect mainly on the mass variable of one hundred grains (MCG), obtaining a linear growth in the values at as there is an increase in water availability in the soil.